Magnetic resonance imaging evaluation of treatment efficacy and prognosis for brain metastases in lung cancer patients after radiotherapy: A preliminary study. Issue 7 (17th May 2018) - Liu, Yuhui; Liu, Xibin; Xu, Liang; Liu, Liheng; Sun, Yuhong; Li, Minghuan; Zeng, Haiyan; Yuan, Shuanghu; Yu, Jinming
Abstract : Background: This study used magnetic resonance imaging (MRI) to monitor changes to brain metastases and investigate the imaging signs used to evaluate treatment efficacy and determine prognosis following radiotherapy for brain metastases from lung cancer. Methods: A total of 60 non‐small cell lung cancer patients with brain oligometastases were selected. MRI scans were conducted before and 3, 6, 9, 12, 18, 24, and 30 months after radiotherapy. The tumor and peritumoral edema diameters, Cho/Cr values, elevation of the Lip peak value, and whether the island ( yu‐yuan ) sign or high‐signal ring were present on T2 fluid‐attenuated inversion recovery (FLAIR) imaging were recorded for each metastasis. Results: The mortality risk was higher the earlier the maximum value of peritumoral edema diameter was reached, when there were fewer island signs, and when brain metastases did not present as tumor progression on imaging. There were significant differences in the average peritumoral edema diameter, apparent diffusion coefficient value, the number of elevated Lip peak values, and the number of T2 FLAIR imaging high‐signal rings in a year after radiotherapy in 14 patients with a survival period < 1 year compared to patients with a survival period > 2 years. Conclusion: After radiotherapy for brain metastases, patients with the island sign had longer survival periods, high‐signal rings in T2 FLAIR, elevated Lip peaks, and reduced apparent diffusion coefficient values, indicating tumor necrosis. Increased diameter of metastases and Cho/Cr > 2 cannot serve as reliable indicators of brain metastasis progression.